2020
DOI: 10.1186/s40560-020-00491-y
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on fibrinolytic therapy in COVID-19: the potential of inhalation therapy against suppressed-fibrinolytic-type DIC

Abstract: A high rate of thrombotic complications, such as pulmonary embolism, has been linked to mortality in COVID-19, and appropriate treatment of thrombosis is important for lifesaving. Although heparin is frequently used to treat thrombotic pathology in COVID-19, pulmonary embolism is still seen in severe cases. Although systemic fibrinolytic therapy is a focus of attention because a thrombotic pathology is the cause of death in severe COVID-19, it should be kept in mind that fibrinolytic therapy might be harmful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Furthermore, bleeders showed higher EXTEM ML after r-tPA infusion and borderline hyperfibrinolysis (median [Q1, Q3], 14% [10%, 18%] versus 6% [5%, 8.5%] P = 0.007). Accordingly, thrombolytic therapy might be harmful in patients with advanced stages of COVID-19, where the hemostatic status changed from hyper- to hypocoagulability and from hypo- to hyperfibrinolysis in case of disseminated intravascular coagulation (DIC) [ 55 ]. An ongoing phase IIa randomized controlled trial is aimed at evaluating the efficacy and safety of different doses of Alteplase (50–100 mg IV) for respiratory failure in patients with COVID-19 (STARS trial) [ 56 ].…”
Section: Potential Implications Of Hypofibrinolysis/fibrinolysis Shutmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, bleeders showed higher EXTEM ML after r-tPA infusion and borderline hyperfibrinolysis (median [Q1, Q3], 14% [10%, 18%] versus 6% [5%, 8.5%] P = 0.007). Accordingly, thrombolytic therapy might be harmful in patients with advanced stages of COVID-19, where the hemostatic status changed from hyper- to hypocoagulability and from hypo- to hyperfibrinolysis in case of disseminated intravascular coagulation (DIC) [ 55 ]. An ongoing phase IIa randomized controlled trial is aimed at evaluating the efficacy and safety of different doses of Alteplase (50–100 mg IV) for respiratory failure in patients with COVID-19 (STARS trial) [ 56 ].…”
Section: Potential Implications Of Hypofibrinolysis/fibrinolysis Shutmentioning
confidence: 99%
“…The degree of anticoagulation can be assessed based on the anti-Xa activity or INTEM/HEPTEM CT-ratio for UFH, anti-Xa activity or NATEM/NAHEPTEM CT-ratio for LMWH, and anti-IIa activity, EXTEM CT, or ECATEM/ECA-test CT for IV direct thrombin inhibitors such as argatroban and bivalirudin [ 65 , 73 , 74 , 85 90 ]. Furthermore, the hemostatic phenotype of COVID-19 patients may change from hyper- to hypocoagulability and from hypo- to hyperfibrinolysis during advanced stages of COVID-19 in case of DIC [ 21 , 55 ]. The combination of rotational thromboelastometry and SCT enables the monitoring of these dynamic changes in COVID-19-associated coagulopathy and its corresponding therapy.…”
Section: Bleeding In Patients With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of the coagulation/fibrinolysis system is an important pathophysiological feature of COVID-19 patients, and it is related to the inflammatory cascade induced by viral infection (5)(6)(7). The diffuse intravascular coagulation (DIC) induced by severe infections often becomes a decisive factor in the death of patients with severe infection (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Both patients had severe diabetes mellitus, chronic renal failure, and hemodialysis as comorbidities, and one patient had been on long-term steroids for lung lesions, complicated by thrombocythemia caused by COVID-19. It has been reported that COVID-19 may cause DIC of the fibrinolytic type from sepsis caused by viral infection, [ 15 ], but only one of our case patients, who had a bleeding tendency, developed DIC. Therefore, it is important to pay attention to the possibility of hemorrhagic complications in high-risk patients.…”
Section: Discussionmentioning
confidence: 56%